La dynamique de la recherche et développement aux Etats-Unis : origines et évolution du système d’innovation américain - Jacques-Henri Coste (Revue LISA)
This article concentrates on the historical transformations of the American system of innovation. It analyses the two major cycles that have shaped the informal and institutional development of research and development in the USA. Open innovation was first launched by individuals then internalized in firms before becoming an institutionalized and integrated mode of industrial and university research known as R&D. During the Second World War, this closed and private mode transformed itself into a national system of innovation overseen by the Federal Government. Changing socio-economic conditions and regulations in the 1980s have caused this governance system to become more open and pluralist, bringing to the fore key stakeholders such as firms, universities, networks, and innovative entrepreneurs. However, the globalization of innovation and the emergence of new competitors are currently challenging the open American model of competition-based innovation.